"Even the Sex and the City girls eat them!"1: A textual analysis of DC Cupcakes and Cupcake Girls. Issue 4 (2nd October 2017) - O'Malley, Donica
ABSTRACT: Although food and media scholars have studied gendered performances on cooking shows, limited scholarship exists on shows that combine food preparation with business ownership. My study, a textual analysis of DC Cupcakes and Cupcake Girls, seeks to fill that gap, pointing to issues of gender representation that are complicated by taking on the dual roles of chef or baker and business owner. I argue that these two shows reinforce heteronormative stereotypes and gender polarization by reproducing negative relationships between women and food and by constructing women as incompetent business people. Additionally, I suggest that because these women are shown as business owners instead of just home cooks, such portrayals could potentially disrupt the dominant, often essentialist ideas about men and women on food television. Instead, however, these shows, as part of the wider cultural cupcake phenomenon, resort to stereotypical portrayals of women and help cultivate their at times oppressive relationships with food.